Determinants of external whistleblowing intentions : Evidence from the Sime Darby Berhad staff / Mohd Rozaimy Ridzuan, Noor Amira Syazwani Abd Rahman and Nur Hidayahtul Nabihah Manas - Ridzuan, Mohd Rozaimy; Abd Rahman, Noor Amira Syazwani; Manas, Nur Hidayahtul Nabihah (Universiti Teknologi MARA Cawangan Pahang, 2019)
Incidences of organisational wrongdoings, such as fraud and corruption in Western giant multinational companies like Enron, WorldCom, Anderson, and Tyco, are increasingly becoming issues of concern. This phenomenon has provided impetus for scholarly studies on whistleblowing, and particularly, the need to explore the reasons behind such problems. This study examines whether the variables such as organizational commitment and status of wrongdoers have significant influenced towards external whistleblowing intentions among Sime Darby staff. This quantitative study focuses on Sime Darby staff by using a hypothesis testing study and utilizing questionnaires to collect the data from the respondents. The empirical study shows that both organizational commitment and status of wrongdoer variables have significant influenced towards external whistleblowing among Sime Darby staff. This study is vital as it supplements the information to the existing body of knowledge on whistleblowing issues in Malaysia.